Suspension by choice: Determinants and asymmetries - Franziska K. Kruse; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2018)
We investigate whether soccer players collect their fifth yellow card and their suspension by choice. Using data for the German Bundesliga for the seasons 13/14 to 16/17, we show that the quality of the player's own team, the quality of the teams participating in the next matches, and whether a team wins or not increase the probability of a player collecting his fifth yellow card.
Keywords: L83; D91; C23; 330; Soccer; decision making; suspension by choice